2014
DOI: 10.18632/oncotarget.1296
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 as a potential metastasis-driving gene in prostate cancer

Abstract: Effective treatment for metastatic prostate cancer is critically needed. The present study was aimed at identifying metastasis-driving genes as potential targets for therapy (oncotargets). A differential gene expression profile of metastatic LTL-313H and non-metastatic LTL-313B prostate cancer tissue xenografts, derived from one patient's specimen, was subjected to integrative analysis using the Ingenuity Upstream Regulator Analysis tool. Six candidate master regulatory genes were identified, including GATA2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…GATA2 is a factor normally involved in hematopoiesis and mutations in GATA2 are seen in myelodysplastic syndrome, acute myeloid leukemia, and chronic myeloid leukemia (Crispino and Horwitz, 2017). However, GATA2 is also associated with prostate cancer (Chiang et al, 2014; Crispino and Horwitz, 2017; He et al, 2014; Xiao et al, 2016). GATA2 is considered to be a pioneer transcription factor that facilitates coactivator recruitment to the androgen receptor transcription complex to regulate a key set of genes related to prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…GATA2 is a factor normally involved in hematopoiesis and mutations in GATA2 are seen in myelodysplastic syndrome, acute myeloid leukemia, and chronic myeloid leukemia (Crispino and Horwitz, 2017). However, GATA2 is also associated with prostate cancer (Chiang et al, 2014; Crispino and Horwitz, 2017; He et al, 2014; Xiao et al, 2016). GATA2 is considered to be a pioneer transcription factor that facilitates coactivator recruitment to the androgen receptor transcription complex to regulate a key set of genes related to prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue microarrays (TMA) were manually constructed, as previously described (37,38), using various Gleason grades-exhibiting prostate cancer specimens (n ¼ 342), obtained from the Vancouver Prostate Centre Tissue Bank with written informed consent of patients, clinical information, and institutional study approval. All specimens were obtained through radical prostatectomy, except CRPC samples that were obtained via transurethral resection of the prostate.…”
Section: Human Prostate Cancer Tma Construction and Ihcmentioning
confidence: 99%
“…The migration and invasion potential of PC-3 cells following treatment with MCT4 ASOs was investigated using Matrigelcoated modified Boyden chambers (BD Biosciences) as previously described (38). Briefly, ASO-treated cells were seeded into the top chamber at 50,000 live cells per well.…”
Section: Modified Boyden Chamber Assaymentioning
confidence: 99%
“…ChIP-on-chip analysis revealed that the GATAbinding motif is enriched in the AR-binding chromatin regions in LNCaP cells (23). GATA2 has been reported to facilitate androgen-responsive gene expression (24) and to promote cell migration, tissue invasion, and metastasis (25). It has been reported that GATA2 can directly regulate AR gene expression in a stable LNCaP cell line with doxycycline-inducible GATA2 (26).…”
Section: Significancementioning
confidence: 99%